STRUCTURAL, ELECTRONIC AND MAGNETIC PROPERTIES OF VANADIUM DOPED DELAFOSSITE CUGAO2: AN AB INITIO STUDY (FUDMA JOURNAL OF SCIENCES, 2024)
Delafossite copper gallium oxide (CuGaO2) is one of the most important copper-based delafossite materials reported. It has variety of applications that include but are not limited to; photo catalysis, dye-sensitized solar cells. However, due to the wide band gap of this material, it appears very attractive as transparent conductive oxide (TCO). Thus, it is very important and applicable in optoelectronic device technologies. In this paper, the structural, electronic and magnetic properties of vanadium (V) doped delafossite CuGaO2 are investigated using first principle study based on density functional theory (DFT) as implemented in the QUANTUM ESPRESSO simulation package. We used Perdew-Burke-Ernzerhof (PBE) generalized gradient approximation (GGA) exchange-correlation scheme for the undoped and vanadium (V) doped structures. There is no structural transition after the doping. The results indicated that the V doping reduced the band gap of the undoped delafossite CuGaO2 by 0.8 eV. It also contributed more to the conduction band states. However, our results also revealed that the 50 % V doping induced significant changes to the magnetic properties of the undoped CuGaO2. It was found that the undoped CuGaO2 is slightly paramagnetic similar to the same group member CuAlO2, whereas the V doped CuGaO2 system is slightly ferromagnetic. This result is in agreement with previous literature concerning the effect of doping semiconductor material with magnetic metals. Thus, based on our results, V doped CuGaO2 material may be considered as an important candidate for spintronics and other related applications.
Keywords: Delafossite; Doping; Ferromagnetic; Transparent conducting oxide; Spintronics; Paramagnetic